Does C1 esterase inhibitor play a role in post COVID-19 neurological symptoms? A randomized, double-blind, placebo-controlled, crossover, proof-of-concept study - Melamed, Isaac; Buckley, Caley; Bayko, Mary Ellen; Williams, Joe Lynn; Or-Geva, Noga (Frontiers in Neurology, 2025)
BackgroundMany patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection experience neurologic changes post-infection, which has been hypothesized to be due to dysregulation in the infectious-immune axis that leads to a neuro-immune response. This immune dysfunction has been termed “Alzheimer’s of the Immune System” or AIS and there are several immune factors that may play a key role. These include, among others, complement activation due to low levels of C1-esterase inhibitor (C1-INH) and function, and a decrease in signaling of Toll-like receptor (TLR)-3. We propose that C1-INH replacement may upregulate the immune dysfunction, thereby improving neurological symptoms.MethodsIn this randomized, double-blind, placebo-controlled, crossover, proof-of-concept study, adults experiencing SARS-CoV-2 post-viral fatigue syndrome for >4 weeks post-recovery from coronavirus disease 2019 (COVID-19) infection were randomized 1:1 to two arms: Arm 1 (C1-INH for 8 weeks, then placebo for 8 weeks) or to Arm 2 (placebo for 8 weeks, then C1-INH for 8 weeks). Patients were assessed for adult executive function, abnormal cognitive decline, depression [Beck Depression Inventory-II (BDI-II)], migraine, fatigue [Fatigue Severity Scale (FSS)] and pain (Short-form McGill Pain Questionnaire). Percent change in TLR signaling in response to zymosan was compared with controls at baseline, Week 8 and Week 16. Safety was assessed throughout.ResultsAt this interim analysis, 36 patients with SARS-CoV-2 post-viral fatigue syndrome had completed the two 8-week treatment periods. In Arm 1, trends toward improvements from baseline at Week 8 of C1-INH therapy were observed in BDI-II score (−8.7 points), mean FSS score (0.6 points), and mean McGill Pain Questionnaire score (−0.4 points). These improvements were either sustained or worsened at Week 16, following crossover to placebo. The outcomes in Arm 2 were compatible with those in Arm 1. Patients with SARS-CoV-2 post-viral fatigue syndrome had low levels of TLR-related signaling biomarkers compared with healthy controls.ConclusionThis proof-of-concept study demonstrates sustained dysregulation of the immune system after COVID-19 infection. Improvements in depression, fatigue, and pain were observed with C1-INH treatment in patients with SARS-CoV-2 post-viral fatigue syndrome, indicating C1-INH may be a potential therapeutic target.Clinical trial registrationThe study was registered on September 21, 2024, with the identifier number NCT04705831.